2002
DOI: 10.1083/jcb.200203150
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the intracellular behavior of HIV in living cells

Abstract: To track the behavior of human immunodeficiency virus (HIV)-1 in the cytoplasm of infected cells, we have tagged virions by incorporation of HIV Vpr fused to the GFP. Observation of the GFP-labeled particles in living cells revealed that they moved in curvilinear paths in the cytoplasm and accumulated in the perinuclear region, often near the microtubule-organizing center. Further studies show that HIV uses cytoplasmic dynein and the microtubule network to migrate toward the nucleus. By combining GFP fused to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
824
3
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(883 citation statements)
references
References 31 publications
45
824
3
6
Order By: Relevance
“…2). This was observed for Reovirus, Adenovirus, HSV, influenza virus and HIV 5,[42][43][44][45] . Viral transport is often highly regulated as with, for example, HSV in neurons.…”
Section: Viral Transportmentioning
confidence: 57%
See 1 more Smart Citation
“…2). This was observed for Reovirus, Adenovirus, HSV, influenza virus and HIV 5,[42][43][44][45] . Viral transport is often highly regulated as with, for example, HSV in neurons.…”
Section: Viral Transportmentioning
confidence: 57%
“…In a recent study, the HIV genome-associated integrase was labelled, and automated 3-dimensional particle tracking revealed that HIV-1 complexes underwent both microtubule-and actin-dependent movements toward the nucleus and more diffuse movements once inside the nucleus 57 . Remarkably, reverse transcription of the HIV genome seems to begin while the virus is being transported to MTOC 44 .…”
Section: Viral Transportmentioning
confidence: 99%
“…1a) (reviewed in refs [124][125][126]). The HIV-1 preintegration complex travels to the nuclear envelope via the microtubule network [127], and is subsequently actively transported through the nuclear pore, although the cis-and trans-acting factors required for nuclear uptake are still debated [128]. Genetic analyses indicate that properly assembled capsids are required for the successful completion of reverse transcription (and other early events) [47,49,50,67,71,129,130] and also for later events that accompany nuclear localization of the preintegration complex [130,131].…”
Section: Capsid Disassemblymentioning
confidence: 99%
“…With this technique, the individual steps of the entry process and the dynamics of these processes can be elucidated. SVT has been utilized to investigate the entry and trafficking of several viruses including adeno-associated virus (Bräuchle et al 2002;Seisenberger et al 2001), adenovirus (Suomalainen et al 1999), simian virus 40 (Damm et al 2005), murine polyoma virus (Ewers et al 2005), HIV (McDonald et al 2002), influenza virus (Lakadamyali et al 2003;Rust et al 2004), rabies virus (Finke et al 2004) and murine leukemia virus (Lehmann et al 2005). From the trajectories of individual viruses, the interactions between these particles and different cellular components can be directly observed.…”
Section: Introductionmentioning
confidence: 99%